PERAN ORANG TUA DALAM MENGENALKAN BAHASA DAERAH KEPADA ANAK MELALUI PENDIDIKAN KELUARGA (Studi Deskriptif Pada Keluarga Di Kecamatan Compreng Kabupaten Subang) - Azizah Faturochmah, - (2022)
This research is motivated by the situation in Kalensari Village and Compreng Village where children have various language abilities. The language used by the child is in accordance with the language of the environment the child first encounters after being born, namely the father's language and mother's language. Often at school children use language that the teacher cannot understand, and vice versa, children also do not understand the language used by the teacher. So that the speaking skills of children at school are still relatively low. The aims of this study are 1) to describe the motivation of parents to introduce local languages to children in the family 2) to describe how parents learn to introduce local languages to children in the family 3) to describe the inhibiting and supporting factors parents introduce regional languages to children in the family. The method used is a descriptive method with a qualitative approach. The data were taken by interview, observation, literature study and documentation study. The results of the study show that 1) there is motivation from outside and inside so that children grow interest and desire to know local languages. 2) The way parents teach local languages is by giving examples, teaching, supervising, controlling and getting used to using local languages. 3) factors that influence the introduction of regional languages in children are economic factors, parental education factors, socio-cultural and religious factors Keywords: Family education, Role of parents, Local language,